Impact of the Invasive Beech Leaf-Mining Weevil, Orchestes fagi, on American Beech in Nova Scotia, Canada - Sweeney, Jonathan D.; Hughes, Cory; Zhang, Honghao; Hillier, N. Kirk; Morrison, Andrew; Johns, Rob (Frontiers in Forests and Global Change, 2020)
The beech leaf-mining weevil, Orchestes fagi (L.), is native to Europe where it commonly attacks European beech. The weevil was discovered infesting American beech in Halifax and Cape Breton Island, Nova Scotia, Canada in 2012, but anecdotal reports of defoliated beech in the Halifax area as early as 2006 suggest it established 5–10 years prior to its discovery. Our objectives were to estimate the impact of O. fagi on American beech in forested sites and urban areas, as well as its economic impact on owners of residential properties with mature American beech. In 2014, we established fifteen 11.28 m fixed radius plots in forested sites containing a total of 260 American beech at Sandy Lake, Oakfield, and Mt. Uniacke (n=5 plots per site), where weevil infestation levels were high, moderate, and nil, respectively. At the same time we recorded the degree of cankering by beech bark disease on the main stems of each tree. Plots were visited annually to record tree mortality (2014–2019) and percentage of leaves with larval mines or adult feeding (2016–2019). We surveyed residents of Halifax in 2016 and 2018 to determine the rate of beech mortality and costs of tree removal in urban residential areas. Between 2016 and 2019, the percentage of leaves mined by weevil larvae increased from 6% to 59% at Mt. Uniacke, from 48% to 83% at Oakfield, and from 87% to nil at Sandy Lake (because there were too few leaves to sample). During the same period, cumulative beech mortality increased from 35% to 48% at Mt. Uniacke, from 10% to 70% at Oakfield, and from 88% to 94% at Sandy Lake. Tree mortality was not associated with severity of beech bark disease, except at Mt. Uniacke which had the fewest years of defoliation by the leaf-mining weevil. Mortality rates were lower in urban areas (32% in 2016, 44% in 2018) but direct costs to property owners who hired arborists to remove dead beech trees were significant, averaging $1934 ($300–$6600) per resident in 2018. Options for mitigating the impact of O. fagi on American beech are briefly discussed.